2016
DOI: 10.1161/strokeaha.116.013970
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and Risk Factors for Cerebral Infarct After Surgical Aortic Valve Replacement

Abstract: Background and Purpose Stroke is a potentially devastating complication of cardiac surgery. Identifying predictors of radiographic infarct may lead to improved stroke prevention for surgical patients. Methods We reviewed 129 post-operative brain MRIs from a prospective study of patients undergoing surgical aortic valve replacement (AVR). Acute infarcts were classified as watershed or embolic using pre-specified criteria. Results Acute infarct on MRI was seen in 79 of 129 patients (61%), interrater reliabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 10 publications
0
17
0
2
Order By: Relevance
“…Of the 109 patients with no stroke and with postoperative brain magnetic resonance imaging, silent infarcts were diagnosed in 54%, but these were not associated with increased in-hospital mortality. These investigators noted that embolic infarcts were associated with aortic arch atheroma (odds ratio [OR] 3.4), old subcortical infarcts (OR 5.5), and higher AV gradient (OR 1.3) [23]. In PARTNER-2A, neurologic assessment was performed routinely and led to a neurologic diagnosis in 6.9% at 30 days and 11% at 2 years.…”
Section: Neurologic Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 109 patients with no stroke and with postoperative brain magnetic resonance imaging, silent infarcts were diagnosed in 54%, but these were not associated with increased in-hospital mortality. These investigators noted that embolic infarcts were associated with aortic arch atheroma (odds ratio [OR] 3.4), old subcortical infarcts (OR 5.5), and higher AV gradient (OR 1.3) [23]. In PARTNER-2A, neurologic assessment was performed routinely and led to a neurologic diagnosis in 6.9% at 30 days and 11% at 2 years.…”
Section: Neurologic Eventsmentioning
confidence: 99%
“…Randomized trials and retrospective studies show equipoise in terms of survival between TAVR and SAVR in intermediate-risk patients [23][24][25]; however, complications such as paravalvular leak, vascular complications, and new pacemaker implantation may remain higher in TAVR, with stroke, bleeding, and acute kidney injury higher after SAVR.…”
Section: Tavr and Savr In Intermediate-risk Patientsmentioning
confidence: 99%
“…Also in agreement with our results, atheromatous plaque is another principal cause of embolism and poorer outcomes during surgery on the aortic valve. 39,40 However, our analysis comparing CABG with and without foramen ovale repair, the main difference being opening of the heart, found that there was a trend but not a significant difference in RAO incidence.…”
Section: Discussionmentioning
confidence: 71%
“…30 Watershed infarcts were defined as one lesion >1.5cm or more than one lesion <1.5cm in either the cortical border zone (CBZ) or the internal border zone (IBZ). The CBZ was defined as the junction between the anterior, middle and posterior cerebral artery territories, and the IBZ as the junction of the anterior, middle, and posterior cerebral arteries with the Hubner, lenticulostriate, and anterior choroidal artery territories.…”
Section: Methodsmentioning
confidence: 99%